84‐3: Invited Paper: Organic Light‐Emitting Diode Beam Shaping: Pixel Design for Variable Angular Emission Profile Control. Issue 1 (30th May 2018) - Fries, Felix; Fröbel, Markus; Ang, Pen Yiao; Lenk, Simone; Reineke, Sebastian
Abstract : Organic light‐emitting diodes (OLEDs) are the leading self‐emitting pixel technology in current and future small and large area displays. Once integrated with a certain layer architecture into the backplane layout, their emission colour and angular distribution is set by the optical properties of the layered system. In this paper, we demonstrate a pixel design that allows for actively controlled variation of the angular emission profile of the individual vertical pixel. For this, a tandem device is developed that comprises two units optimized for different angular emission pattern. We constrained the system to operate in a narrow emission band to maintain monochromaticity of the individual pixel. We discuss this concept for a red phosphorescence‐based OLED stack and give an outlook based on simulations for the other primary display colours green and blue. The tandem unit can be operated with only two electrodes making use of the AC/DC driving concept, where the outer electrodes are in direct connection. In this paper, we will discuss the potential, status, and technology challenges for this concept.